State Health Insurance Mandates and Labor Market Outcomes: New Evidence on Old Questions - Yaa Akosa Antwi; J. Catherine Maclean (Institute of Labor Economics (IZA), 2017)
In this study we re-visit the relationship between private health insurance mandates, access to employer-sponsored health insurance, and labor market outcomes. Specifically, we model employer-sponsored health insurance access and labor market outcomes across the lifecycle as a function of the number of high cost mandates in place at labor market entrance. Our analysis draws on a long panel of workers from the National Longitudinal Survey of Youth 1979 and exploits variation in five high cost state mandates between 1972 and 1989. Four principal findings emerge from our analysis. First, we find no strong evidence that high cost state health insurance mandates discourage employers from offering insurance to employees. Second, employers adjust both wages and labor demand to offset mandate costs, suggesting that employees place some value on the mandated benefits. Third, the effects are persistent, but not permanent. Fourth, the effects are heterogeneous across worker types. These findings have implications for thinking through the full labor market effects of health insurance expansions.
Keywords: H2; I13; J3; 330; mandated benefits; labor costs; health insurance